A microdroplet-accelerated Biginelli reaction: mechanisms and separation of isomers using IMS-MS. Issue 18 (3rd April 2019) - Sahota, Navneet; AbuSalim, Deyaa I.; Wang, Melinda L.; Brown, Christopher J.; Zhang, Zhicaho; El-Baba, Tarick J.; Cook, Silas P.; Clemmer, David E.
Abstract : Electrospray ionization (ESI) combined with ion mobility spectrometry (IMS) and mass spectrometry (MS) techniques is used to examine the Biginelli reaction in an ensemble of ions generated from droplets. Abstract : Electrospray ionization (ESI) combined with ion mobility spectrometry (IMS) and mass spectrometry (MS) techniques is used to examine the Biginelli reaction in an ensemble of ions generated from droplets. We find evidence for rapid dihydropyrimidinone formation from condensation of ethyl acetoacetate, benzaldehyde, and urea on the very short timescales associated with the electrospray process (∼10 μs to ∼1.0 ms). Control bulk-solution reactions show no product formation even after several days. This implies that the in-droplet reaction rate is enhanced by an astonishing factor. Examination of the reaction conditions and characterization of the intermediates en route to product shows evidence for variations in the reaction mechanism. IMS separation shows that the Knoevenagel condensation intermediate from benzaldehyde and ethyl acetoacetate exists as both the cis - and trans -isomer, in a ∼5 to 1 ratio. We suggest that the dramatic acceleration arises because of increased reagent confinement as electrosprayed droplets shrink. The ability of IMS-MS to resolve intermediates (including isomers) provides a new means of understanding reaction pathways.